2018
DOI: 10.4103/ijdr.ijdr_215_16
|View full text |Cite
|
Sign up to set email alerts
|

An orthopantomographic study of prevalence of hypodontia and hyperdontia in permanent dentition in Vadodara, Gujarat

Abstract: There was a high prevalence of hypodontia and a low incidence of hyperdontia in the studied population. Prompt diagnosis of these anomalies can help plan treatment modalities at an early age to establish a functional and esthetic dentition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
21
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 0 publications
7
21
0
4
Order By: Relevance
“…Numerous studies have reported that tooth agenesis is more common in the mandible than in the maxilla (6,7,16,18), and these results were in agreement with our results. However, other studies have shown that the tooth agenesis was dominantly in the maxilla (8,15,17).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Numerous studies have reported that tooth agenesis is more common in the mandible than in the maxilla (6,7,16,18), and these results were in agreement with our results. However, other studies have shown that the tooth agenesis was dominantly in the maxilla (8,15,17).…”
Section: Discussionsupporting
confidence: 93%
“…In this research, agenesis of the second lower premolar was most common, followed by the upper lateral incisor, upper second premolars and lower central incisors. Most other studies confirmed the same (3,5,6,8,(16)(17)(18), in contrast to some studies, where the upper lateral incisor was the most commonly affected tooth (11). Generally, agenesis of certain teeth was more prevalent in female subjects (Figure 3), which is related to the overall prevalence of tooth agenesis in our sample.…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…In the present study the prevalence of supernumerary teeth in Mongoloid children of Manipur in North East India has been found to be 0.9%. Interestingly this is similar to the prevalence reported in other parts of India which were 0.9% in study done by Mahabob et al and 0.7% in study done by Saha et al but lower as compared to 1.3% as reported by Sharma et al and 2.97% as reported by Soni et al [6][7][8][9] . The prevalence found in this study was found to be higher as compared to a study by Shilpa et al who reported a prevalence of 0.21% in primary dentition 10 .…”
Section: Discussionsupporting
confidence: 88%